Kristus Sebagai Adam Kedua Menurut Hilarion Alfeyev: Proses Menuju Pembaharuan - Hia, Generasi (GENEVA: JURNAL TEOLOGI DAN MISI, 2024)
This article aims to analyze the perspective of Jesus as the second Adam in the book Orthodox Christianity Doctrine and Teaching of the Orthodox Church. Jesus Christ as the second Adam is the word of God who came and took on the nature of man to replace and redeem mankind who had fallen into sinfulness due to the disobedience of the first Adam who had violated the commandments of God. Because of the disobedience of the first Adam, human nature itself was polluted by sin, resulting in human beings being unable to receive and experience the grace of God. The perspective of Jesus as the second Adam provides an important point that the first Adam experienced total failure due to disobedience but the second Adam who came as a human being restored human nature that had been polluted by sin and provided a renewal. So that when humans are increasingly renewed in Christ, they will automatically receive eternal life with God. In this research, the author uses a literature study method that analyzes and reads one book as the main source of research that leads to a conclusion that Jesus as the second Adam restores and brings renewal to all humanity.